No Poverty and No Hunger as Achievements in Implementing the SDGs Economic Pillar - Maulana, Lucky Hikmat; Aminda, Renea Shinta; Syaiful, Syaiful; Pratama, Erik; Kusumawati, Riny (Moneter: Jurnal Keuangan dan Perbankan, 2023)
The realization of the implementation of the Sustainable Development Goals (SDGs) in the economic pillar is represented by the goal of development without poverty and without hunger, the achievement of which is expected to decrease further by 2030. Implementation of indicators in goal 1 and goal 2 of the Regency SDGs Bogor, which has been implemented according to the regional action plan during the 2020-2022 period, was observed for its achievements using descriptive explanation methods and qualitative analysis of achievement of indicator targets in Bogor Regency. The study results show that policy implementation in Bogor Regency looks very good, especially in reducing poverty rates, increasing health service rates, and reducing stunting and work programs. Apart from that, the activities of all Regional Apparatus Organizations in the Bogor Regency Government have led to the achievement of sustainable development goals, especially SDGs goal 1 and goal 2 as part of the economic pillar.